Cellulose ethers and cement paste permeability. (June 2015) - Pierre, Alexandre; Perrot, Arnaud; Picandet, Vincent; Guevel, Yann
Abstract: Cellulose ether (CE) admixtures are used to improve the water retaining properties of cement-based materials in order to ensure their homogeneity during casting operations. Water permeation through concrete is usually quantified by permeability. In this study, an oedometric cell has been adapted to investigate the influence of CE dosage on the permeability of fresh cement pastes. The purpose-designed device has to allow the filtration of CE aggregates through the oedometric filters and retain cement particles. Simultaneous rheological shear flow measurements have been carried out to evaluate the viscosities of the initial interstitial liquid and the percolated fluid that has filtrated through the fresh cement paste. Comparison of both viscosities allows the evaluation of the amount of CE adsorbed by the cement particles over a wide range of CE dosage. Moreover, the analysis of experimental results confirms previous studies concerning the improvement of water retaining ability due to CE that in turn limits the amount of bleed water. Comparison of an apparent viscosity computed from permeability measurements and viscosity computed from rheological measurements shows that CE strongly modifies the particle networks above the overlap concentration. The results of this study suggest that CE aggregates are formed and plug part of the cement paste porosity. As a result, the apparent viscosity increases and leads to a strong decrease in the material's apparent permeability. Finally, apparent permeabilities are reported for CE dosages ranging from 0% to 0.5%. The results of the study show that combination of rheological and permeability measurements offers a promising method to analyze how CE acts on fresh cement pastes, that are subjected to a hydraulic gradient induced by casting processes.